2019
DOI: 10.1007/s10953-019-00887-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Head Group Effect on Critical Micelle Concentration of Cationic Surfactants Using Molecular Connectivity Indices and Atomic Partial Charges

Abstract: The influence of the head group structure on the critical micelle concentration of cationic surfactants, mainly quaternary ammonium bromide salts with one alkyl tail, has been studied theoretically by QSPR using molecular connectivity indices and also the atomic partial charges. Two models obtained allow to study the effect of head group structure modification on the value of the critical micelle concentration. The model, which contains molecular connectivity indices together with the charge localized on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Among the factors known to affect the cmc value in aqueous solution is the structure of the surfactant [1]. Therefore, as shown in many articles [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], the critical micelle concentration can be predicted directly from the structure of the molecule by quantitative structure-property relationship analysis, in short QSPR. The first correlation was given by Klevens [19] who empirically found that the logarithm of cmc linearly decreases with the increase in the number of carbon atoms in the surfactant alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors known to affect the cmc value in aqueous solution is the structure of the surfactant [1]. Therefore, as shown in many articles [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], the critical micelle concentration can be predicted directly from the structure of the molecule by quantitative structure-property relationship analysis, in short QSPR. The first correlation was given by Klevens [19] who empirically found that the logarithm of cmc linearly decreases with the increase in the number of carbon atoms in the surfactant alkyl chain.…”
Section: Introductionmentioning
confidence: 99%